Exploration of Librarians' Assertive Behaviour in Improving Service Quality in the Digital Age - Mufti Zevira; Sri Rohyanti Zulaikha (ASTEEC, 2024)
This article explores the assertive behaviour of librarians in an effort to improve service quality in the digital era. It is expected that librarians can adjust to the rapid development of technology and the increasingly complex demands of users. To face these challenges, assertive behaviour is required, which includes effective communication skills, the ability to express opinions assertively, and self-confidence. This research uses the literature study method to look at various scientific sources on assertive behaviour and its impact on library service quality. The results show that assertive behaviour helps create good interactions between librarians and users, increases user satisfaction with services, and supports the transformation of libraries towards digital-based services. It is hoped that this research will provide insights for librarians on how to develop assertive skills to improve the quality of services provided by digital libraries.